The Paradox of Knowledge-Intensive Entrepreneurship in Low-Tech Industries Evidence from Case Studies of the German Textile Industry - Schwinge, Isabel; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2015)
This book presents the first multidimensional investigation of KIE in the context of low-tech industries and gives insights in paradox conditions and specific mechanisms, using the example of the German textile industry. Therefore, the author solves conceptual inconsistencies and develops an alternative framework referring to systemic concepts of sectoral innovation systems and KIE as well as to the concept of institutional entrepreneurs. As a result, the deviation of willful actors from a restricting institutional environment and sources of entrepreneurial opportunities can be investigated more comprehensively.  Contents • The Sectoral Innovation System of the German Textile Industry • The German Textile Industry as an Example The Emergence of Knowledge-Intensive Entrepreneurship in Low-Tech Industries Target Groups • Students and lecturers of economic sociology and economics • Decision makers in industrial policies and economic promotion  The Author During her PhD, Isabel Schwinge researched and lectured at the Chair of Economic and Industrial Sociology, TU Dortmund University.
Keywords: Economic sociology; Political economy; Sociology; Organizational Studies, Economic Sociology; International Political Economy; Knowledge - Discourse